Posthumanist Technologies in Business: AI and Cloud Computing for Global Optimization and Ethical Challenges - Rodriguez Barboza, Jhonny Richard; Oscar David Carreño-Flores; Luis Miguel Davila-Zamora; Hans Manuel Jalixto-Erazo; Miguel Alfonso Oré de los Santos; Orlando John Cruces-Torres; Ricardo Edmundo Ruiz-Villavicencio; Danny Villegas-Rivas (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
. This study explores the integration of artificial intelligence (AI) and cloud computing within posthumanist technologies, focusing on their impact on business optimization and information security. A systematic review of 40 studies across sectors such as banking and retail highlights the benefits of AI in automating tasks and enhancing decision-making, while cloud computing provides flexibility and scalability. However, risks like data privacy issues, algorithmic bias, and cybersecurity vulnerabilities demand attention. The research emphasizes the need for ethical frameworks and security strategies to mitigate these risks. Additionally, it stresses the importance of equitable access to these technologies for small and medium-sized enterprises (SMEs) and marginalized communities. The study provides actionable recommendations for businesses and calls for future research on the long-term societal implications of these technologies